Does the Miller-Modigliani Dividend Irrelevance Theory Apply to Portuguese Companies? - Silva, Amandio F. C. da (Journal of Ecohumanism, 2024)
Miller and Modigliani´s theories have been studied and discussed by many researchers, but are based on optimal market conditions, where there are no transaction costs or taxes involved. These assumptions are not true to any modern market. One of the most famous theories of M-M is the dividend irrelevance theory, where the authors argued that dividends do not make any difference to the share prices, whether paid or not. This theory too was the target of several researchers, some of them defending it, others criticizing it. This article analyzes their theory based on optimal market conditions and after considering the fact that market deals attract transaction costs and taxes, by testing it on the Euronext Lisbon Portuguese Stock Index (PSI) for the period of 2019-2023. The results prove that M-M´s theory does not apply to the Euronext Lisbon PSI, as the prices tend to change for dividend paying companies, between the cum-dividend date and the ex-dividend date.